A Study on Cultural Research about the Community of Human Destiny: With the Point of “Love” in Confucianism and Mohism - Ming Qin, Yan Guo (Forest Chemicals Review, 2022)
This paper focuses on the thought of "community of human destiny" with the background of existing researches and tries to explore its ideological origin from the level of cultural tradition. In terms of etymology, “The Community of Human Destiny” is a composite concept formed by the combination of “Human Destiny” and “The Community”, namely, that human destiny is shared by wholly human. From the cultural perspective, “The Community of Human Destiny” has a profound cultural foundation, both Confucianism and Mohism spirit are connected closely with this thought. The Confucian family principle in traditional Chinese culture takes “self cultivation - family harmony - governing the country - world peace “as the developmental path, among which self-cultivation is the fundamental task. The whole way progressively with the beginning of the self-construction of internality and then extrapolate to the construction of the world. Mozi’s principle of benefiting the world directly gives the forms of how people relate to each other, that is, by means of “mutual respect”, to “mutual benefit” propels to realize the mutualistic symbiosis in the world. Through above analysis, the results is that the idea of “the community of human destiny” can be understood as the creative development of traditional cultural heritage in the modern and contemporary times.